Persepsi Pengguna mengenai Mitigasi Krisis Pelecehan Seksual di KRL Jabodetabek: - - Dachlan, Mohammad Zulfikar; Sudarto, Sudarto; Pratiwi, Aprilianti; Halim, Bonny Perkasa (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2026)
Sexual harassment and sexual violence within the Jabodetabek KRL Commuter Line services have evolved into a serious organizational crisis for KAI Commuter. This study aims to analyze passengers’ perceptions of the effectiveness of the crisis mitigation system developed by KAI Commuter, particularly from the perspective of gender-sensitive crisis communication. Employing a descriptive qualitative approach, the research utilized in-depth interviews with three active KRL users to collect primary data, which were subsequently analyzed using the Situational Crisis Communication Theory (SCCT). The findings indicate that users generally appreciate KAI Commuter’s mitigation measures, including the provision of women-only carriages, the implementation of AI-based analytical CCTV systems, blacklisting policies for perpetrators, and multi-platform reporting channels. However, the study also identifies several critical gaps: (1) limited public literacy regarding official complaint channels, particularly the 021-121 call center; (2) uneven and inconsistent dissemination of mitigation efforts; (3) organizational responses that remain highly dependent on the virality of cases; and (4) the need to strengthen the empathy and responsiveness of frontline officers. These findings confirm that the effectiveness of the rebuild and diminish strategies within SCCT largely depends on the organization’s ability to directly reach and build trust with users, rather than relying solely on institutional communication. This study contributes to the development of a user experience-based crisis communication model within the context of public transportation in Indonesia.